Comparative analysis of graded blends of palm kernel oil, palm kernel stearin and palm stearin. (15th July 2019) - Liu, Chunhuan; Meng, Zong; Chai, Xiuhang; Liang, Xinyu; Piatko, Michael; Campbell, Shawn; Liu, Yuanfa
Highlights: Both PKO/POs and PKS/POs blends showed eutectic behavior. PKO/PKS blends displayed good compatibility and only slightly monotectic effect at high temperature (above 30 °C). Ternary blends (PKO/PKS/POs) showed eutectic effects, especially at high temperature (25 and 30 °C). POs addition elevated phase transition temperature, and accelerated the β crystal formation. Abstract: A comprehensive analysis of graded binary and ternary blends of palm kernel oil (PKO), palm kernel stearin (PKS) and palm stearin (POs) was conducted, including solid fat content, iso-solid diagram, thermal properties, polymorphism and microstructure. Both PKO/POs and PKS/POs blends showed eutectic behavior. While PKO/PKS blends displayed good compatibility and only slightly monotectic effect at high temperature (above 30 °C). POs addition elevated binary phase transition temperature and accelerated the β crystal formation. PKO/POs and PKS/POs binaries showed β′ polymorphism, β and β′ polymorphism, and β polymorphism with different POs additions, while all of PKO/PKS blends showed β′ polymorphism. Ternary blends (PKO/PKS/POs) showed eutectic effects, especially at high temperature (25 and 30 °C). POs addition made ternary blends undergo a polymorphism transformation from β′ to β. Our findings open up the possibility of non-hydrogenated fat products as well as develop specific food formulations.